The Relevance of the Concept of Livelihood to Contemporary Muslim Society:: A Holistic Thematic Study - Rafi', Ghazy Abiyyu (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2026)
Social and economic transformations in contemporary Muslim societies have influenced the understanding of the concept of maintenance (nafkah) in Islamic family law. Classical fiqh constructions that position the husband as the sole provider emerged from specific patriarchal social contexts and often encounter tension when confronted with the realities of modern, more egalitarian family structures. This study aims to examine the substance of the concept of nafkah in Islamic family law and to explain its relevance in responding to contemporary social dynamics. This research employs a normative-conceptual approach with a thematic-holistic analysis of scriptural texts and a maqāṣid al-syarī‘ah perspective. Data were collected through library research and analyzed using qualitative descriptive methods. The findings indicate that the substance of nafkah lies not in who performs the role of breadwinner, but in its function as an economic responsibility to ensure family welfare and sustainability. The relevance of the concept of nafkah in the modern context is reflected in the flexibility of economic role distribution between husband and wife based on the principles of reciprocity, justice, and public interest, in accordance with the objectives of maqāṣid al-syarī‘ah.